Analisis Pendapatan Usaha Budidaya Kepiting Soka (Scylla Serrate) Di Kecamatan Pangkalan Susu Kabupaten Langkat - Ansari Priska Damayanti; Siti Mardiana; Endang Sari Manullang (Mahesa Research Institute, 2024)
Soka crabs are one of the livelihoods for the people of Pang kalan Susu District, Langkat Regency, where most of the people are quality crab breeders. The increasing demand for Soka crabs and consumer demand for Soka crabs brings a special attraction to efforts to form Soka crabs through cultivation. With the high demand for soft-shelled crabs, it encourages researchers to examine the income analysis of soft-shell crab cultivation in Pangkalan Susu District,Langkat Regency. The purpose of this study was to analyze the effect of seed costs, amount of feed, cage costs and labor costs on the income of Soka crab (Scyllaserrata) cultivationin Pangkalan Susu District, Langkat Regency. The results showed that the labor cost variable had a significant effect on the income of Soka crab cultivators, but the variable cost of seeds, the amount of feed and the cost of cages had no significant or significant effect on the income of Soka crab cultivators. The average income of Soka crab farmers per month is Rp. 1,808,494, with the average production cost incurred by cultivators per month is Rp. 2.583.978, so that the average income of cultivators per month is Rp. 1.808.494 with a cage area of 1,000 m2.